2013
DOI: 10.1152/ajplung.00184.2013
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of N-linked glycosylation promotes proteasomal degradation of the human ATP-binding cassette transporter ABCA3

Abstract: The lipid transport protein, ABCA3, expressed in alveolar type 2 (AT2) cells, is critical for surfactant homeostasis. The first luminal loop of ABCA3 contains three putative N-linked glycosylation sites at residues 53, 124, and 140. A common cotranslational modification, N-linked glycosylation, is critical for the proper expression of glycoproteins by enhancing folding, trafficking, and stability through augmentation of the endoplasmic reticulum (ER) folding cycle. To understand its role in ABCA3 biosynthesis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 62 publications
6
32
0
Order By: Relevance
“…N-linked glycosylation is one of the most common co-/posttranslational modifications that occurs during protein synthesis in the ER/Golgi and has been shown to have a pivotal role in the folding, stability, and cellular localization of proteins (Helenius and Aebi, 2001; Beers et al, 2011; Molinari, 2007). Cleavage profiles, generated using endoglycosidase H (Endo H) and N-gylycosidase F (PNGase F) that cleave N-linked glycans including complex carbohydrate chains, have confirmed the structural predictions that ABCA3 undergoes N-linked glycosylation (Cheong et al, 2006; Matsumura et al, 2006; Beers et al, 2013). Subsequent site directed mutagenesis studies have demonstrated that substitution mutations of asparagine to alanine at either or both of the 124 and 140 residues resulted in ER retention of glycan deficient ABCA3 isoforms and showed increased electrophoretic mobility of the expressed products by immunoblot (Beers et al, 2013).…”
Section: Functional Domains Of Abca3mentioning
confidence: 78%
See 1 more Smart Citation
“…N-linked glycosylation is one of the most common co-/posttranslational modifications that occurs during protein synthesis in the ER/Golgi and has been shown to have a pivotal role in the folding, stability, and cellular localization of proteins (Helenius and Aebi, 2001; Beers et al, 2011; Molinari, 2007). Cleavage profiles, generated using endoglycosidase H (Endo H) and N-gylycosidase F (PNGase F) that cleave N-linked glycans including complex carbohydrate chains, have confirmed the structural predictions that ABCA3 undergoes N-linked glycosylation (Cheong et al, 2006; Matsumura et al, 2006; Beers et al, 2013). Subsequent site directed mutagenesis studies have demonstrated that substitution mutations of asparagine to alanine at either or both of the 124 and 140 residues resulted in ER retention of glycan deficient ABCA3 isoforms and showed increased electrophoretic mobility of the expressed products by immunoblot (Beers et al, 2013).…”
Section: Functional Domains Of Abca3mentioning
confidence: 78%
“…Following synthesis of the primary translation product and translocation to the ER, ABCA3 is routed via the Golgi, sorting vesicles (SVs), and multivesicular bodies (MVBs) directly to the outer membrane of LBs in AT2 cells or to lysosomes and lysosomal-related organelles in A549 and HEK293 cell lines (Cheong et al, 2006; Mulugeta et al, 2002; Nagata et al, 2004; Beers et al, 2013). Functionally essential posttranslational modifications including glycosylation and proteolytic cleavage also occur during this trafficking (discussed below).…”
Section: Biosynthesis Of Abca3mentioning
confidence: 99%
“…Although the molecular mechanism of protein aggregation still needs to be elucidated, disruption of glycosylation is a potential factor that contributes to the degradation of proteins and their aggregates. For example, N-linked glycans on ABCG2 (ATP-binding cassette transporter) and ABCA3 (the lipid transport protein) have been shown to be important for protein stability, and disruption of N-linked glycosylation results in these proteins' destabilization, as well as enhanced degradation through the proteasome (Beers et al, 2013;Nakagawa et al, 2009). Moreover, proteins are also degraded through the autophagy-mediated lysosomal pathway (Ishida et al, 2009;Vembar and Brodsky, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…O-linked glycosylation occurs at a serine (Ser) or threonine (Thr) residue by the attachment of N-acetylgalactosamine (Peter-Katalinic, 2005). Site-directed mutagenesis of glycan linked-amino acids (Asn, Ser or Thr) in a protein reduces its glycosylation and can disrupt its biological functions (Beers et al, 2013). However, mutations in non-glycan-linked amino acids could also lead to glycosylation defects.…”
Section: Introductionmentioning
confidence: 99%
“…For example, missense mutations in the ABCA3 extracellular domain 1 (ECD1) location were classified as Type II mutations because specific ABCA3 missense mutations in ECD1 were experimentally shown to lead to the accumulation ABCA3 protein in the endoplasmic reticulum. 17,20 The same process was extended to mutations in extracellular domain 2 (ECD2). However, frameshift and nonsense mutations that were located in the nucleotide binding domain 1 (NBD1) were classified as Type I mutations as mutations of this type result in defective protein synthesis.…”
Section: Classification Criteriamentioning
confidence: 99%